Creep rates of spray ice - Shields, D.; Domaschuk, L.; Funegard, E. (Canadian Geotechnical Journal, 1990)
Mars Island, a man-made spray ice island, was constructed in January and February 1986, and was used as a drill platform for petroleum exploration in the Alaskan Beaufort Sea. A series of pressuremeter creep tests was run in the spray ice of Mars Island in March 1986. Individual constant-pressure tests lasted up to 5 days.It is possible to compare the creep behaviour of the spray ice as interpreted from the pressuremeter tests with the creep behaviour interpreted from the island settlement records. These comparisons are made for both primary and secondary creep on the basis of conventional power law theory. The following points are of particular interest: (1) The primary creep data can be characterized using a simple power law. The exponent of time for spray ice is similar to that for solid polycrystalline ice. The exponent of stress is different for the two kinds of ice. (2) Pressuremeter tests gave secondary creep information that correlates well with the steady-rate settlement of the island. (3) Research into the possible range of primary creep parameters for spray ice is required, given that primary creep accounted for a large portion of the settlement of Mars Island. In particular, the effect of ice density on creep rates mast be resolved. (4) The pressuremeter is potentially an excellent design control device during the manufacture of future spray ice islands. The results of constant-pressure tests of 1–2 days duration could be used to check the design assumptions pertaining to the expected consolidation of the ice mass with time. Key words: spray ice, creep, artificial islands, pressuremeter, settlement.